FROM CYBORG TO CYBERNANTROPHE: BASIC POLITICAL, CULTURAL AND PHILOSOPHICAL DIMENSIONS OF THE CONCEPTS - Stojanović, Đorđe (The Policy of National Security, 2023)
This paper will provide an overview and critically examine the underlying political, cultural and philosophical dimensions of artificial intelligence through the analysis of current theoretical variants of the idea of humanism: from posthumanism and transhumanism, through antihumanism to digital humanism. At the same time, the concept of digital humanism is favored, which is affirmative of both the achievements of modern technologies and the spirit/reason of humanity.
Keywords: posthumanism; transhumanism; artificial intelligence; cyborg; cyberanthrope